Post-diapause synthesis of ArHsp40-2, a type 2 J-domain protein from Artemia franciscana, is developmentally regulated and induced by stress. - Nathan M Rowarth; Thomas H MacRae (PLoS ONE)
Post-diapause cysts of Artemia franciscana undergo a well-defined developmental process whereby internal differentiation leads to rupture of the cyst shell, release of membrane-enclosed nauplii and hatching to yield swimming larvae. The post-diapause development of A. franciscana has been examined at biochemical and molecular levels, yet little is known about molecular chaperone function during this process. In addressing this we recently described ArHsp40, a type 1 J-domain protein in post-diapause A. franciscana cysts and larvae. The current report describes ArHsp40-2, a second J-domain protein from A. franciscana. ArHsp40-2 is a type 2 J-domain protein, lacking a zinc binding domain but containing other domains characteristic of these proteins. Notably, ArHsp40-2 possesses a double barrel β-domain structure in its substrate binding region, as does ArHsp40. qPCR revealed a relatively low amount of ArHsp40-2 mRNA in 0 h cysts which increased significantly until the E1 stage, most likely as a result of enhanced transcription, after which it declined. An antibody specific to ArHsp40-2 was produced and used to show that like its mRNA, ArHsp40-2 accumulated until the E1 stage and then decreased to amounts lower than those in 0 h cysts. The synthesis of ArHsp40-2 was induced by heat shock indicating that ArHsp40-2 is involved in stress resistance in cysts and nauplii. Accumulation in cysts during early post-diapause development followed by its sharp decline suggests a role in protein disaggregation/refolding, a function of Hsp40s from other organisms, where ArHsp40-2 assists in the rescue of proteins sequestered during diapause by p26, an abundant small heat shock protein (sHsp) in A. franciscana cysts.